Pengaruh Motif Pengguna Media Terhadap Kepuasan Mengakses Konten Youtube Narasi Newsroom Sebagai Media Berbasis Digital - Hidayat, Ihsan Mughni; Khoyin, Muh.; Prajitno, Subagio Budi (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2024)
This research aims to provide in-depth insight into the preferences of digital media user. The theory used is the Uses and Gratification theory. This research uses a positivism paradigm with a quantitative approach and methods. survey using a questionnaire. The sampling technique used was purposive sampling, with the population consisting of students from the Faculty of Da'wah and Communication class of 2020. The research sample consisted of 47 students. The research results showed that the Information and Integration and Social Interaction motives partially influenced audience satisfaction with the Narasi Newsroom program. The low significance value indicates that these motives have a significant influence in increasing audience satisfaction with the program on Narasi TV.